Urgensi Sertifikasi Produk Halal Perspektif Maqasid Al-Syariah Al-Ghazali - Maksum, Muh (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Maqasid Al-Syariah is the initial gateway that must be passed in order for Islam to become a religion that is able to realize benefits and implement its expectations as a religion that is relevant to current developments. To realize benefits in the form of a halal lifestyle, a guarantee is needed that covers all needs for a halal lifestyle. In Indonesia, to realize this guarantee, a law was issued requiring all products in circulation to be halal certified by BPJPH (Halal Product Guarantee Organizing Agency). This research aims to describe the objectives and wisdom of establishing mandatory rules for halal product certification using Al-Ghazali's maqasid al-syariah theory. This research is a type of qualitative library research (library study) which is carried out by collecting data and information from various sources contained in the literature. This research results in the conclusion that the obligation to certify halal products is oriented towards Al-Ghazali's maqasid al-syariah, namely bringing benefit and rejecting harm. Halal product certification is included in maqasid al-syariah which is related to religion and the world and is based on five principles of benefit, namely protecting religion, soul, reason, lineage and property.